Study of the Relationship Between Students' Biology Learning Outcomes and Students’ Family Environment - Yunita, Deni (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to analyze the relationship between students' biology learning outcomes and their family environment. This study also aims to identify family environmental factors that contribute to students' biology learning achievement. Methodology: This research is a quantitative research with descriptive method. The population in this is XI science at Public High School 2 Bengkulu, 40 students, and parents of each student is 40 people. The sample was taken using saturated sampling technique. The research instrument used family environment questionnaire, observation, and documentation and data analysis techniques used were descriptive statistics and inferential statistics. Main Findings: The results of the analysis show that the family environment has a significant influence on the learning outcomes of class XI science students in the inferential statistical analysis with the F test showing that the calculated F value is greater than the F table, which means that the relationship between the family environment and student learning outcomes is significant. The average results of the family environment are the moderate category, while student learning outcomes are in the very high category. Novelty/Originality of this study: This research focuses on class XI science students, offering a special understanding of how the family environment relationships learning outcomes in biology at a critical educational stage. This can provide in-depth insight into the factors that relationship academic performance at the upper secondary education level. Seeing the relationship of the family environment on biology learning outcomes.